The Collaboration Model of Stakeholders Perspective Implementation of Prostitutional Prevention and Handling Policy - Nurul Umi Ati (Khazanah Sosial, 2022)
The phenomenon of human trafficking for commercial sexual exploitation has long been developed in various countries, including Southeast Asia, such as Indonesia. Prostitution prevention and handling efforts can be carried out by the government through the formulation of policies or regulations and implemented with a collaboration of various government actors and non-government actors, both national, regional, and local stakeholders. This research aims to study the collaboration model of stakeholders in the perspective of implementation of prostitutional prevention and to handle policy in Surabaya as the closure of Dolly, the largest prostitution area in Southeast Asia. In conclusion, state collaboration with the community in handling prostitution will be a strong root because here will create a synergy together to always supervise and seek mutual solutions in preventing and handling the problem of prostitution, so that can be an example for other local governments in making prevention and handling policies of prostitution in their region. The method used in this research is the experimental method. The first step is a survey to get research subjects. The survey was conducted using the snowball method. Researchers also evaluated several potential groups. Then the process is continued by using a SWOT analysis to determine the best pilot location. Participatory Focus Group Discussion and interviews to deepen the diagnosis. The diagnostic results are developed and compiled manually. This study found that the main causes of prostitution were mostly related to family problems, personal problems, the trauma of sexual harassment, and unemployment. The existence of teenagers who fall into prostitution is a social problem in society. The negative impact is moral degradation. Implications of research to strengthen the Social work profession to prevent prostitution and provide clear and factual information about the reasons why young people may fall into prostitution. This solution should involve both formal and informal institutions.